Incipient speciation in allopatric Etheostoma rupestre (Percidae: Etheostomatinae) lineages, with the description of three new subspecies - Hilburn, Bryson G.; Janosik, Alexis M.; Johnston, Carol E. (Zootaxa, 2023)
In recent years, new species descriptions for the North American darters have proliferated. Most species concepts accepted by contemporary ichthyologists require that a valid species be both monophyletic and diagnoseable, yet many lineages exhibit modal or range differences in morphological characteristics without individuals being diagnosable. Such scenarios present difficulties with regards to proper taxonomic recognition of divergent lineages and often prohibit appropriate conservation action. Following the example of recent authors, we provide meristic, geometric morphometric, and pigmentation data to support the recognition of three subspecies of Etheostoma rupestre, a species endemic to the Mobile Basin. These morphological data cohere with previous genetic work for E. rupestre. The nominate subspecies Etheostoma rupetsre rupestre (Tsai’s Rock Darter) is endemic to the Tombigbee River and Black Warrior River watersheds in Alabama and Mississippi and is characterized by having lower numbers of lateral blotches, lower range and mean of lateral line scales, lower modal number of scales above the lateral line, and lower degrees of nape squamation than other subspecies. Etheostoma rupestre piersoni (Shamrock Darter), ssp. nov., is endemic to the Cahaba and Alabama River Watersheds in Alabama and is characterized by intermediate counts of lateral blotches and higher scale counts and nape squamation than E. r. rupestre. Etheostoma rupestre uphapeense (Jade Darter), ssp. nov., is restricted to several small, disjunct populations in the Coosa and Tallapoosa watersheds in Alabama, Georgia, and Tennessee. Etheostoma r. uphapeense is characterized by having a higher mean number of lateral blotches than both other subspecies and higher scale counts than E. r. rupestre. While E. r. rupestre and E. r. piersoni are widespread and abundant within their respective ranges, E. r. uphapeense has a disjunct range and is often uncommon where it occurs. Etheostoma r. uphapeense should be monitored where it occurs to discern population trends.